Strategi Guru dalam Mengembangkan Apresiasi Siswa Seni Ukir Gebyok melalui Pendidikan Berbasis Budaya Lokal - Wulandari, Fiska Noviana; Fajrie, Nur; Najikhah, Fatikhatun (JPKS (Jurnal Pendidikan dan Kajian Seni), 2024)
There is a problem at SD Muhammadiyah Blimbingrejo where students lack knowledge about local culture, even though aspects of regional cultures are sometimes gradually introduced during the teaching and learning process. This research aims to analyze the strategies used by teachers to enhance students' appreciation of the Gebyok carving art within the context of local culture-based education at SD Muhammadiyah Blimbingrejo, Jepara. The research uses a qualitative approach with a case study, collecting data through observation, interviews, and documentation. The results show that teachers play a crucial role in introducing, teaching, and integrating the Gebyok carving art into the curriculum, allowing students to understand and appreciate their local cultural heritage. Additionally, this approach helps in developing students' positive attitudes towards local culture, which is important for preserving cultural heritage and strengthening national identity.